PENEGAKAN HUKUM TINDAK PIDANA PENCURIAN DI DALAM ANGKUTAN UMUM OLEH KEPOLISIAN RESOR KOTA PEKANBARU - Putra, Rangga Prayudha; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
In line increases of people's income, many people buy their personal vehicles. With the number of private vehicles on the road it will cause traffic jam. So there are many people who use public transport to travel. However, here appears distorted mind and the opportunity for criminals on public transport, especially theft. The high demand of the economy and lack of jobs is also the reason why crimes occur on public transport. Rampant theft in public transport makes the user of public transport did not feel safe and comfort.There are several types of public transport in the city of Pekanbaru, namely city transport, city bus, trans metro and taxi. Theft is the most often crime happens in the public transpotation. The crimes can happen at the all time, it can happen anytime and anywhere. There are many crimes that occur on public transportation and city buses.In this case the law enforcers have tried to combat the crime, one of them with the process of law against the perpetrators to trial and criminal sanctions imposed in accordance with applicable laws, but it is very difficult for authorities to tackle the problem of crime, thisproofed by the lack of law enforcement especially weak police officers in performing their duties and obligations. The impression or the public image of the police in almost every country still has not improved. Failure to tackle crime will be the target of criticism and public censure.The weakness of law's implementation was caused by the persistence of the constraints and challenges in matter of law, the legal apparatus, facilities and infrastructure as well as other factors that influence it. Although the legal development takes time, but the need for the law to shelter not be delayed even prove the people's demand is constantly increasing, and should be recognized also there are the excesses in the application and enforcement.Keywords: Law Enforcement - Crime of Theft - Public Transport